Psychometric Properties of the Italian Version of the Short-Form Supportive Care Needs Survey Questionnaire (SCNS-SF34-It): A Multicenter Validation Study - Anita Zeneli; Paolo Leombruni; Marco Miniotti; Emanuela Scarpi; Marco Maltoni; Sara Cavalieri; Valentina Legni; Cristina Nanni; Mihaiela Tarca; Michela Rustignoli; Sandra Montalti (MDPI AG, 2024)
This study aimed to evaluate psychometric properties of the Italian version of the Short-Form Supportive Care Needs Survey Questionnaire (SCNS-SF34) in a cancer population. A multicenter prospective observational study was carried out in outpatient and inpatient settings. The evaluated psychometric properties were as follows: the five-domain structure, the internal consistency, the convergent validity with the Edmond Symptom Assessment System (ESAS) questionnaire, the discriminant validity and test-retest reliability. A total of 714 patients with different types, stages and treatment settings of cancer were recruited. A total of 56% of participants were women, the median age 59 years (range 18-88). The prevalence of patients reporting at least one unmet need was 78.7%. The factor analysis explained 71.3% of the total variance, confirming the five-domain structure of the original model. Internal consistency was good, with Cronbach's alpha values ranging from 0.87 ("psychosocial need", "patient support and health system", "information") to 0.90 ("sexuality"). The convergent validity of the SCNS-SF34-It with the ESAS scale was low, suggesting that these questionnaires cover different concepts. The SCNS-SF34-It was able to discriminate differences between groups, and the test-retest reliability was good (ICC 0.72-0.84). The SCNS-SF34-It proved to be a reliable instrument for use in clinical practice for evaluating unmet needs in the Italian population of cancer patients. This study was not registered.